Governance Matters: Boosting Firm Value Through Profitability: Tata Kelola Perusahaan: Meningkatkan Nilai Perusahaan Melalui Profitabilitas - Difandika Yudi Firmansyah; Wida Purwidianti; Naelati Tubastuvi; Iwan Fakhruddin (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to explore the moderating role of good corporate governance in the relationship between financing decisions, investment decisions, dividend policy, and profitability on firm value. Utilizing a purposive sampling technique, we analyzed data from 85 manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2022, resulting in 195 unbalanced observations. Employing regression modeling with panel data, we conducted descriptive statistical tests, preliminary tests (Breusch-Pagan, Chow, and Hausman tests), diagnostic tests (heteroscedasticity and autocorrelation), and hypothesis testing. The findings reveal that while profitability positively influences firm value, financing, investment, and dividend decisions do not significantly impact it. Furthermore, good corporate governance enhances the relationship between profitability and firm value, with the presence of female directors contributing to increased profitability. However, female directors do not moderate the effects of financing, investment, and dividend decisions on firm value. This research underscores the importance of female leadership as a mechanism of good corporate governance in enhancing company value